Introducing sustainability in engineering education curricula: an achievable outcome or a utopia? - Alves, Anabela Carvalho (2017)
Sustainability, social and environmental responsibility become more and more relevant for professional engineering. This is recognized by universities that are doing their best to introduce these issues in the curricula. But this is not a trivial issue and their integration with the existent and news issues must be total. So, a lot of authors, academics, researchers are always concerned with this and are trying different approaches and learning methodologies in order to achieve successfully sustainability integration. This paper presents and explores some of these approaches and perspectives from four different countries: Portugal, Brazil, Canada and Spain. The study is based on the analyses of papers, presentations and debate session results from a previous engineering education conference. In spite of the reduced sample, it was a lived sample that shared personal and team perspectives about the issue through the debate. Also, it is discussed how the participants introduced sustainability, corroborating that this integration could be an achievable outcome and not a utopia.